Strategi Bawaslu dalam Mencegah Praktik Politik Uang pada Pemilu Tahun 2024 di Kabupaten Serdang Bedagai (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the Bawaslu Strategy in Preventing Money Politics Practices in the 2024 Election in Serdang Bedagai Regency. The interesting thing in this study is because the phenomenon of money politics is increasingly rampant during the democratic party even though there is an election supervisory body (Bawaslu) whose job is to supervise the election process, but the problem of money politics has not been resolved until now. The type of research used by the author is qualitative research. With a qualitative descriptive approach to examine more deeply the understanding of Bawaslu's strategy in preventing money politics practices in general elections. The data collection technique used in this study uses observation, interview and documentation techniques. The location of this research is at the Serdang Bedagai Regency Bawaslu office located in Sei Rampah. Respondents in this study are sources who are experts in the field of study being studied, so the sources chosen are the chairman, secretary and members of the Serdang Bedagai Regency Bawaslu who are in the prevention and handling division. The results of this study indicate that Bawaslu's strategy in preventing money politics practices in the 2024 election in Serdang Bedagai Regency was declared successful and running effectively according to the expected goals. The strategy carried out by Bawaslu is to conduct socialization activities to the community about the dangers of money politics, make billboards with the slogan